2020
DOI: 10.18585/inabj.v12i4.1220
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Acetylcholinesterase (AChE) Inhibitor and the Association with Hypertension among Farmers in Bandung, Indonesia

Abstract: BACKGROUND: The use of acetylcholinesterase (AChE) insecticides is still widely used by farmers in flower and agricultural centers. However, biological monitoring of farmers is still very rare in Indonesia. AChE inhibitors are reported to have toxic effects on various organs.METHODS: This study involved 120 subjects in Cihideung, Cikole and Pangalengan areas. All subjects have been interviewed, physically examined and biological sample taken by medical team. Descriptive analysis was performed to assess general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Those with cholinesterase levels < 1.30 U/g, which were in the reference risk range and those with cholinesterase levels ≥ 1.30 U/g were within the normal reference range. (Mulyana et al, 2020) The results revealed that the results of screening for the enzyme cholinesterase in the blood among farmers were in risk level (66.7%) and normal level (33.3%; (Andrea Guytingco, Phayong Thepaksorn, & Richard L Neitzel, 2018; Mulyana et al, 2020) In accordance with research conducted in Indonesia and Thailand. However, this study aligns with the research of (Rosanti, Rahma, & Hamawi, 2021) which discovered that there were six farmers at very high risk, 17 farmers at high risk, 26 farmers at medium risk, and eight farmers at low risk of pesticide contamination.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Those with cholinesterase levels < 1.30 U/g, which were in the reference risk range and those with cholinesterase levels ≥ 1.30 U/g were within the normal reference range. (Mulyana et al, 2020) The results revealed that the results of screening for the enzyme cholinesterase in the blood among farmers were in risk level (66.7%) and normal level (33.3%; (Andrea Guytingco, Phayong Thepaksorn, & Richard L Neitzel, 2018; Mulyana et al, 2020) In accordance with research conducted in Indonesia and Thailand. However, this study aligns with the research of (Rosanti, Rahma, & Hamawi, 2021) which discovered that there were six farmers at very high risk, 17 farmers at high risk, 26 farmers at medium risk, and eight farmers at low risk of pesticide contamination.…”
Section: Discussionsupporting
confidence: 71%
“…The results were analyzed by the Faculty of Medicine at Ramathibodi Hospital Bangkok. (Mulyana et al, 2020) Blood Cholinesterase levels were divided into two categories: the risk level (<1.30 U/g) and normal level (≥1.30 U/g). (Mulyana et al, 2020)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood cholinesterase levels were categorized into two groups: at risk (levels below 1.30 U/g) and normal (levels at or above 1.30 U/g). This classification was based on the cut-off value for the enzyme, which is below the limit of detection value used for biomonitoring AChE among farmers in Bandung, Indonesia [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pesticide poisoning of farmers can be identified from the preparation of equipment, mixing pesticides, spraying, cleaning tools and work clothes, cleaning grass and pests, watering plants as well as harvesting (Mulyana et al, 2020). Furthermore, pesticides can enter the body through the skin (dermal), exhalation (inhalation), or mouth (oral).…”
Section: Introductionmentioning
confidence: 99%